Transformasi Lahan Sempit Menjadi Ruang Hijau Produktif Melalui Kebun Mini - Syakur, Abdan; Resky Ilmayanti, Andi; Putri Ramadhani, Arista; Juita; Aswardi, Muh.; Asfan As, Muhammad; Amsis, Nurcholifha; Mulyani, Rizki; Nadhifah, Yahyun (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The Community Service Program in the Field of Education (KKN-DIK) conducted by Universitas Muhammadiyah Makassar was implemented in Bontomangape Village, Galesong District, Takalar Regency, from August 4 to October 9, 2025. This program aimed to empower the local community through education and practical activities in transforming narrow land into productive green spaces in the form of mini gardens. It also served as a learning platform for students to apply educational knowledge in real community contexts.The implementation methods included several stages: preparation, execution, counseling, mentoring, and evaluation. The preparation stage involved coordination with the community and site surveys. The execution phase covered land clearing, preparation of planting media, and planting various crops such as chili, tomato, eggplant, and moringa leaves. The counseling and mentoring stages focused on educating the community about the importance of greening, the process of making organic fertilizer, and sustainable plant care techniques.The results showed strong enthusiasm and active participation from the community throughout the program. The mini gardens successfully grew and became not only a source of beauty but also of food and learning for the residents. Moreover, the program enhanced community awareness of the importance of environmental sustainability and strengthened the relationship between students and local residents through participatory educational activities.